PENGARUH BRAND IMAGE, LABELISASI HALAL, DAN KUALITAS PRODUK TERHADAP LOYALITAS PRODUK PADA PELANGGAN TSABITA HALAL BOGA GENTAN SUKOHARJO - Anggraini Saraswati; Suprayitno Suprayitno; Lamidi Lamidi (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
To face fierce competition, food industry business players must have a competitive advantage. This research is a survey research. This type of data uses qualitative data and quantitative data. The data source uses primary data and secondary data. The population in this study were customers of Tsabita Halal Boga Gentan Sukoharjo who had made purchases more than 2 times. The number of samples used was 100 people, using accidental sampling technique. The data technique used questionnaires and observations. The data analysis used descriptive analysis and multiple linear regression test. The results showed that brand image has a significant effect on customer loyalty Tsabita Halal Boga Gentan Sukoharjo, halal labeling has a significant effect on customer loyalty Tsabita Halal Boga Gentan Sukoharjo, product quality has a significant effect on customer loyalty Tsabita Halal Boga Gentan Sukoharjo.